1994
DOI: 10.1177/095148489400700206
|View full text |Cite
|
Sign up to set email alerts
|

Waiting Lists in the Post-Review NHS

Abstract: Waiting lists for hospital inpatient treatment have existed since the foundation of the NHS. There have been many theories put forward to explain them and a wide range of proposals have been advanced to reduce or eliminate them. The effect of the recent changes in the NHS, coupled with the renewed political focus on waiting lists, is explored. It is concluded that access to waiting lists may be restricted, either by explicit rationing or as a result of contractual specifications. Further, the introduction of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Another positive contextual-level government factor identified in the literature was the involvement of stakeholders, including professional associations [22,25,26], partners such as national or provincial health ministries [22,24-27,54], patients, and other stakeholders in the health network [22,56]. Methods for involving stakeholders, which included soliciting them for information on data [37], advice on existing processes, ideas for improvements [25,26,32], and recommendations [24,26], as well as ensuring systems for reporting [37], were seen as helpful for WTMS implementation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another positive contextual-level government factor identified in the literature was the involvement of stakeholders, including professional associations [22,25,26], partners such as national or provincial health ministries [22,24-27,54], patients, and other stakeholders in the health network [22,56]. Methods for involving stakeholders, which included soliciting them for information on data [37], advice on existing processes, ideas for improvements [25,26,32], and recommendations [24,26], as well as ensuring systems for reporting [37], were seen as helpful for WTMS implementation.…”
Section: Resultsmentioning
confidence: 99%
“…At the contextual level, tools included instruments or procedures that affected more than one organization, such as the development and implementation of standards and guidelines [22-27,33-35,40,44,52,56]. Some procedures involved standardizing equipment across hospitals ( e.g .…”
Section: Resultsmentioning
confidence: 99%
“…Demand for public hospital elective surgery usually exceeds the supply of beds and staff, so hospital administrators use waiting lists to manage backlogs and to contain costs. 5 Access is therefore prioritised according to need: 6 patients are added to a list in chronological order, but are moved up or down the queue depending on clinical urgency. Given that waiting lists are primarily created to support internal management and to assist surgeons in clinical decisions, care should be exercised when using them as indicators of performance.…”
Section: Health Performance Indicators and Waiting Listsmentioning
confidence: 99%
“…The available literature on admission planning and waiting lists is rather extensive; see, e.g., Gemmel and van Dierdonck [4] for a recent state of the art on admission planning and Mullen [8] for a review on waiting lists and waiting list management. Many of the studies reported in [4] are concerned with improving the scheduling of admissions and resources.…”
Section: Introductionmentioning
confidence: 99%
“…All the studies reported regard the level of scheduling of admissions, and do not address the service concept behind the scheduling technique, which is the focus of our study. Mullen [8] gives a state of the art overview on waiting lists and waiting list management. Many of the studies reported deal with prioritisation, i.e., the order in which patients are selected from the waiting list.…”
Section: Introductionmentioning
confidence: 99%